Therapeutic effects of platelet-derived extracellular vesicles on viral myocarditis correlate with biomolecular content - Beetler, Danielle J.; Giresi, Presley; Di Florio, Damian N.; Fliess, Jessica J.; McCabe, Elizabeth J.; Watkins, Molly M.; Xu, Vivian; Auda, Matthew E.; Bruno, Katelyn A.; Whelan, Emily R.; Kocsis, Stephen P. C.; Edenfield, Brandy H.; et al. (Frontiers in Immunology, 2025)
IntroductionExtracellular vesicles (EVs) can potently inhibit inflammation yet there is a lack of understanding about the impact of donor characteristics on the efficacy of EVs. The goal of this study was to determine whether the sex and age of donor platelet-derived EVs (PEV) affected their ability to inhibit viral myocarditis.MethodsPEV, isolated from men and women of all ages, was compared to PEV obtained from women under 50 years of age, which we termed premenopausal PEV (pmPEV). Because of the protective effect of estrogen against myocardial inflammation, we hypothesized that pmPEV would be more effective than PEV at inhibiting myocarditis. We injected PEV, pmPEV, or vehicle control in a mouse model of viral myocarditis and examined histology, gene expression, protein profiles, and performed proteome and microRNA (miR) sequencing of EVs.ResultsWe found that both PEV and pmPEV significantly inhibited myocarditis; however, PEV was more effective, which was confirmed by a greater reduction of inflammatory cells and proinflammatory and profibrotic markers determined using gene expression and immunohistochemistry. Proteome and miR sequencing of EVs revealed that PEV miRs specifically targeted antiviral, Toll-like receptor (TLR)4, and inflammasome pathways known to contribute to myocarditis while pmPEV contained general immunoregulatory miRs.DiscussionThese differences in EV content corresponded to the differing anti-inflammatory effects of the two types of EVs on viral myocarditis.